« Voir les voix » : les Juifs d’Égypte, d’une rive l’autre - Michèle Baussant (Conserveries Mémorielles)
This article focuses on the Jews of Egypt and how they rebuild their connections to Egypt from several spaces and contexts of exile. Based on a "retroactive ethnography," it relies on work with memory and the memory of the Jews of Egypt encountered both as actors and narrators and is interested in the crossed constructions of the presence and absence of Jews and Egyptians. To do so, he explores the persistence and relevance of certain traces, practices, and concrete memories of the past in their relationship to material spaces - what we might call the memory of the inhabited. It also focuses, through return journeys, on the confrontation with the ignorance or silence of the Egyptians who today occupy the various spaces where the Jews lived, frequented, and left their traces: what one might call the uninhabited of memory. These traces, journeys, exchanges between Egyptians and Egyptian Jews reveal the discrepancy and the encounter of displaced histories of people "without traces" and persistent traces of a past as "without history."